مشكلات القيادة المدرسية بمدارس التعليم العام المدمج بها ذوات الإعاقة بمنطقة نجران من وجهة نظر المعلمات والمشرفات وقائدات المدارس - عبدالنبي، فادية رزق عبدالجليل (المركز القومي للبحوث غزة, 2022)
هدفت الدراسة إلى التعرف على مشكلات القيادة المدرسية بمدارس التعليم العام المدمج بها ذوات الإعاقة بمنطقة نجران من وجهة نظر المعلمات والمشرفات وقائدات المدارس، والكشف عن الفروق في درجة مشكلات القيادة المدرسية بمدارس التعليم العام المدمج بها ذوات الإعاقة تبعا لمتغيري (المؤهل العلمي، والخبرة التدريسية)، استخدمت الباحثة المنهج الوصفي التحليلي، وتمثلت الأداة في استبانة طبقت على عينة مكونة من (104) من المعلمات والمشرفات وقائدات المدارس، وكشفت نتائج الدراسة أن مستوى مشكلات القيادة المدرسية بمدارس التعليم العام المدمج بها ذوات الإعاقة بمنطقة بنجران جاءت بمتوسط (3.06 من 5) أي بدرجة (متوسطة)، وعلى مستوى الأبعاد؛ حصل بعد المشكلات المتعلقة بالوسائل التعليمية على أعلى متوسط (3.17) ثم المشكلات المتعلقة بقائدة وقيادة المدارس بمتوسط (3.14) وثالثا مشكلات القبول الاجتماعي للطالبات ذوات الإعاقة بمتوسط (3.14) ورابعا مشكلات المناهج المدرسية بمتوسط (3.02) وخامسا مشكلات اللوائح والقوانين المنظمة بمتوسط (2.97) وأخيرا؛ المشكلات المتعلقة بمعلمات ومشرفات التربية الخاصة بمتوسط (2.94) وجميعها بتقدير لفظي (متوسطة)، وكشفت عن وجود فروق ذات دلالة إحصائية في مشكلات القيادة المدرسية بمدارس التعليم العام المدمج بها ذوات الإعاقة؛ تعزى لمتغيري: المؤهل التعليمي والخبرة، لصالح المؤهل الأقل، والخبرة الأقل، واستنادا للنتائج قدمت الباحثة جملة من التوصيات، وهي ضرورة الحرص على التطوير المهني للمعلمات والمشرفات وقائدات المدارس الذين على رأس العمل. عمل برامج تدريبية لتوضيح أهمية الدمج لذوي الإعاقة، إعادة النظر في اللوائح والقوانين من قبل لجنة السياسات التربوية المنظمة لدمج لذوي الإعاقة في وزراه التعليم، تطوير المناهج الخاصة بدمج ذوي الإعاقة من قبل خبراء ومتخصصين في ذوي الاحتياجات الخاصة. The study aimed to identify the problems of school leadership in integrated public education schools with women with disabilities in the Najran region from the point of view of teachers, supervisors and school leaders, and to reveal the differences in the degree of school leadership problems in public education schools in which women with disabilities are integrated according to the variable: , educational qualification, and teaching experience, The study used the descriptive analytical method, and this study was applied to a sample of (104) out of (104) teachers, supervisors and school leaders. The two researchers used a questionnaire about the problems of school leadership in schools of integrated public education with women with disabilities, and the results of the study revealed that the level of school leadership problems in schools of public education that are integrated with women with disabilities in the Najran region came to a medium degree with an average of (3.06) from the point of view of teachers, supervisors and school leaders. It also found that the dimension of school leadership problems related to educational aids came in the first place, followed by the problems of school leadership related to school leaders and leadership, and after problems related to the social acceptance of students with disabilities, followed by problems related to school curricula, followed by problems related to regulations and laws, followed by problems related to female teachers and supervisors of special education, and revealed the existence of statistically significant differences in the problems of school leadership in the schools of general education integrated with women with disabilities that are attributed to the variable of educational qualification and experience, in favor of the lower qualification and the least experience
Keywords: الإدارة المدرسية -- التنمية المهنية -- الإعاقة العقلية -- السعودية